FGF-Mediated Axon Guidance: Role of Downstream Signaling Pathways in Cytoskeletal Control - Jiyuan Li; Hanqi Gao; Fang Liu (Cells)
Axon guidance, a fundamental process in neural circuit formation, is intricately regulated by Fibroblast Growth Factors (FGFs) and their receptors (FGFRs) through dynamic cytoskeletal remodeling. FGF signaling, mediated by heparan sulfate proteoglycans or Klotho co-factors, activates key downstream pathways: PI3K-Akt, JAK-STAT, PLCγ, and RAS-MAPK. These pathways orchestrate actin filament dynamics, microtubule stability, and the organization of intermediate filaments. These pathways converge on Rho GTPases, cofilin, profilin, and tau to balance the cytoskeletal assembly−disassembly cycles, enabling growth cone navigation. Unresolved questions, such as the mechanisms underlying FGF-mediated growth cone steering, highlight critical future research directions. This review integrates structural, molecular, and functional insights into how FGF-FGFR interactions regulate axon pathfinding, emphasizing the crosstalk between signaling cascades and cytoskeletal plasticity. Elucidating these mechanisms not only advances our understanding of neural development but also opens therapeutic avenues for neuro-developmental disorders, nerve injury, and neurodegenerative diseases by targeting FGF-driven cytoskeletal dynamics.